(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
Turning to the ethnographic record, this paper evaluates how, and if, Being and Time (Heidegger, 1962) supports clinical practice in multicultural therapeutic settings. It problematises an existentialist interpretation of Heidegger’s text, asking whether we, as therapists in practice, should embrace a fixed ontology or rather strive to be ontological?